Improved in situ performance testing of line-concentrating solar collectors: Comprehensive uncertainty analysis for the selection of measurement instrumentation. (15th December 2016) - Zirkel-Hofer, Annie; Perry, Stephen; Fahr, Sven; Kramer, Korbinian; Heimsath, Anna; Scholl, Stephan; Platzer, Werner
Highlights: Guideline for the proper selection of measurement instrumentation is presented. Results assure representative performance testing of concentrating collectors. Detailed methodology is proposed and applied to exemplary uncertainty case study. Complete range of different collector types and operating conditions is studied. One relevant gap of current testing standard for line-concentrating collectors is closed. Abstract: Accurate and complete performance evaluation is playing a major role in the further development of concentrating solar collectors. To ensure dependable test results, an appropriate testing and evaluation procedure is required. Moreover, the selection and installation of suitable measurement instrumentation are essential for obtaining reliable data for the performance evaluation. The quality of the measurement instrumentation greatly influences the representativeness of the test results. Details on the measurement instrumentation recommended for the testing of low-temperature solar collectors have already been provided in the testing standard EN ISO 9806:2013. Due to the larger dimensions of concentrating collectors and thus different working temperatures and mass flow rates, these recommendations cannot be directly applied for the testing of concentrating solar collectors. A good selection of measurement instrumentation will always be a trade-off between feasibility, cost of the instrumentation and its associated uncertainties. For this reason, it is crucial for every testing and certification institution to assess the quality of measurement data during the instrumentation selection process. Until now, this aspect has been sparsely addressed in the relevant literature concerning collector testing procedures. However, uncertainty examinations have become particularly relevant for in situ testing, in which the choice of measurement instrumentation has to be adapted to the specific measurement situation on-site. In situ testing is considered to be particularly beneficial (if not even indispensable) for concentrating collectors in terms of cost effectiveness and feasibility. With the objective of simplifying the selection of measurement instrumentation, we present an elaborate methodology and comprehensive case study concerning the uncertainty calculation of line-concentrating solar collectors. The assessment of the suitability of measurement instrumentation is conducted based on two operational reference cases. These cases adequately cover the complete range of collector types and operating conditions typically involved in the field of line-concentrating solar collectors. The analysis is designed such that the results are also transferable to other testing situations, which are not specifically studied within this publication. The presented systematic uncertainty case study thus serves as a guideline for the selection of appropriate measurement instrumentation, providing useful indications for every testing and certification entity dedicated to the planning and execution of significant and reliable collector performance testing. The associated risk decrease of performance testing is essential for the further development and economic aspects of concentrating solar technology.